2021
DOI: 10.1088/1755-1315/761/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Improving The Quality of Ground Water in Some Areas of Al-Anbar Governorate by Recharging with Rainwater

Abstract: Artificial groundwater recharged with rainwater is the most popular technique for groundwater quality and quantity. Nevertheless, it is still a challenge for researchers to provide precise quantification of groundwater quality and quantity enhancement by recharging with rainwater due to variations in groundwater quality factors such as topography, hydrogeological phenomenon, availability of rainwater, land use pattern, etc. An attempt is being made here to extract the improvement of groundwater quality by addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Research [9] dealt with groundwater assessments for some wells in Al-Khafajia village west of Anbar Province. Research [27] also studied the improvement methods of groundwater quality in some areas of the Anbar Province. The present research aimed to evaluate the study area's water quality by looking at the physical, chemical properties and enriching studies related to groundwater in the Al-Qaim district.…”
Section: Introductionmentioning
confidence: 99%
“…Research [9] dealt with groundwater assessments for some wells in Al-Khafajia village west of Anbar Province. Research [27] also studied the improvement methods of groundwater quality in some areas of the Anbar Province. The present research aimed to evaluate the study area's water quality by looking at the physical, chemical properties and enriching studies related to groundwater in the Al-Qaim district.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment planning should be conservative & symptomatic. In contrast, in case of failure to achieve and return the lesion to a regular oral health status, the oral contraceptive pills should be discontinued or changed in consultation with the gynecologist for another mode of contraceptive method [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, (15) pointed out that the harvest index values in the oat crop differed by varieties and genetic composition. Finally when spraying amino acid, the treatment of amino acid spray recorded the highest average grain protein synth, this is may be due to the fact that free amino acid when added is a source of essential nitrogen in the construction and formation of protein and enzymes and energy processing for vital processes (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…tryptophan gave the highest number of hooks at 3.92and 5.56 plant -1 enables, and the highest average dry weight of 4.39 and 6.42 g, The average weight of the grain was highest at 2.85 and 5.18 g, and the highest average grain snob was 55.48 and 69.44 snabel -1 grains. In the EL-Bassiouny 3 study, the average protein content was found to have increased by 18.52% as a result of paper spraying of tryptophan at a concentration of 50 mg -1 liters. Ethylene gas is a growth defect commonly used in grain crops, added to the plant in the form of spraying, and its effect depends on the spraying time and plant growth stage.…”
Section: Introductionmentioning
confidence: 98%